Seasonal endocrine changes in steroid hormones of developing ovarian follicles in Surti buffaloes - PARMAR, A P; MEHTA, V M (The Indian Journal of Animal Sciences, 2013)
The effect of development of ovarian follicles and seasons on oestradiol-17 beta and progesterone levels was studied in Surti buffaloes. The peak oestradiol-17 Beta levels were recorded influid coUected from follicles 5-8 mm in diameter. The progesterone level in follicular, fluid tended to increase with the increase in folliculardiameter. Significantly lower (p